EVALUATION OF PHYTOCHEMICAL COMPOUNDS, ANTIOXIDANT AND ANTIBACTERIAL ACTIVITY ON RED FRUIT PEEL AS FEED ADDITIVES - altandjung, ririen indriawaty (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
ABSTRAKRed fruit (Pandanus conoideus Lamk) is a native plant from Papua that contains many bioactive compounds such as tocopherol, alpha tocopherol, carotenoids, and flavonoids as well as phenolic, which are potential as antioxidant and antibacterial agents. Red fruit also contains unsaturated fatty acid especially oleic acid (omega-9) which is useful for improving nutritional status of the community along with its mineral contents of Fe, Ca and Zn. The results of this study showed that red fruit peel contains phenolic and flavonoid compounds with test results of 652,49 mg GAE/100g and 143,08 mg/100g respectively. Red fruit peel  has antioxidant activity with IC50 value of 75,785 µg/gr. Antibacterial activity of red fruit peel has a weak inhibition zone but significantly have a good inhibition to Escherichia coli, Salmonella typhi and Lactobacillus plantarum bacteria (P <0,01).Key words: Red fruit peel, phenolic, flavonoid, antioxidant activity, antibacterial activity